INNOVATIVE IT SOLUTIONS FOR ENHANCING TRANSPARENCY IN CUSTOMS AUTHORITIES: INTERNATIONAL EXPERIENCE (World Bulletin of Management and Law, 2026)
The article examines foreign models of applying information technologies in the anti-corruption activities of customs authorities in the context of the digital transformation of public administration. The main areas of the use of digital and information and communication technologies in the activities of customs administrations of various countries are analyzed, aimed at preventing, detecting, and minimizing corrupt practices. The study explores such tools as electronic declaration systems and electronic document management, automated risk management systems, analytical platforms for big data processing, technologies of interagency information interaction, as well as elements of artificial intelligence and automation of control procedures. Special attention is paid to issues of increasing the transparency of customs operations, reducing the influence of the human factor, and strengthening institutional control. Based on a generalization of foreign experience, conclusions are drawn regarding the significance of information technologies in the formation of an effective anti-corruption framework and the possibilities for adapting the examined models in the practical activities of customs authorities.